Tindak Pidana Pencurian Kendaraan Bermotor dalam Perspektif Kriminologi - Nugraha, Fahrul Triana (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2023)
The crime of robbery is a troubling phenomenon that exists in society, in this example the item of a motorized automobile. Looking at criminology, it is trying out and observing how a criminal offense can arise through thinking about diverse aspects, one in every of that's the prison and socio-monetary aspects. Criminology perspectives the crime of motor automobile robbery as an unavoidable social phenomenon, however criminology additionally gives to proportion efforts to cope with it to the foundation of the problem. It is likewise a sequence withinside the traditional judicial agreement that will become unavoidable. Efforts to take a look at criminology had been additionally achieved to look how powerful the punishment withinside the crook justice device turned into according with what he had done. The study approach uses descriptive evaluation. The outcomes of the evaluation which have been achieved withinside the case of the crime of motor automobile robbery: criminological research of the crime of motor automobile robbery, criminological responses to the conviction of perpetrators of the crime of motor automobile robbery, instances which have been processed through regulation had been analyzed the use of a restorative justice approach. The inspiration for this example is to observe the traditional crook device through undertaking a criminology, the want for involvement among the parties, specifically the wrongdoer and the sufferer to create mutual justice.